HUBUNGAN KEPATUHAN DIET HIPERTENSI DENGAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI POLI PENYAKIT DALAM RSUD Prof.Dr.SOEKANDAR MOJOKERTO - Heri Triwibowo; Heni Frilasari; Indah Rachma Dewi (STIKes William Booth Surabaya, 2016)
Hypertension patient compliance still pretty low. Improved compliance can reduce cardiovascular disease mortality caused one method that can be used to improve compliance with measuring blood pressure is. This study aimed to analyze the existence of hypertension diet compliance relationship with blood pressure in patients hipertensi.metode this study is cross-sectional design. Sampling technique in this research is the consecutive sampling samples are partly taken from the whole object under study and are considered representative of the population. Based on the test results using a chi-square statistic. Based on the tabulated results can be expressed ho rejected because the results of the calculation of significance (α) = 0.000. Assuming if ρ <0.05 then ho is rejected so therecorrelation compliancewith blood pressure diet hypertension hypertension in patients at poly space medicine hospital prof. Dr. Soekandar mojokerto. Compliance diet hypertension hypertension patients are mostly (compliance). It is influenced by personal characteristics, experience and enough knowledge about things to do to maintaintheir health.